Randomised, double blind comparison of omeprazole and cimetidine in the treatment of symptomatic gastric ulcer. Issue 10 (October 1989) - Bate, C M; Wilkinson, S P; Bradby, G V; Bateson, M C; Hislop, W S; Crowe, J P; Willoughby, C P; Peers, E M; Richardson, P D
Abstract : In a randomised, double blind, parallel group study in patients with symptomatic gastric ulcer (94% greater than or equal to 5 mm diameter), 102 received omeprazole 20 mg om and 87 cimetidine 400 mg bd. After four weeks 73% and 58% (p less than 0.05) respectively had healed (eight weeks: 84% and 75%, ns). After four weeks, a greater proportion (81%) of omeprazole treated patients was symptom free than of those receiving cimetidine (60%; p less than 0.01). Over the first two weeks, patients receiving omeprazole had less day pain, less night pain and took fewer antacids than those receiving cimetidine (all p less than 0.05). The difference between omeprazole and cimetidine was not appreciably affected by age, smoking, size of the ulcer and trial centre. Tolerability was similar in the two treatment groups. In the treatment of symptomatic gastric ulcer, omeprazole relieves the symptoms more quickly than cimetidine and heals a greater proportion of ulcers within four weeks.